Permanence des impensés de la lutte contre le sida et nécessité d’une pensée critique - Frédéric Le Marcis (Genre, Sexualité et Société, 2013)
This paper is a commentary of an article by Randall Packard and Paul Epstein entitled "Epidemiologists, Social Scientists, and the Structure of Medical Research on Aids in Africa. » Published in 1991 in Social Science & Medicine, this paper constitutes a step in the critical reflexion on both the politics of knowledge and on the fight against HIV and AIDS, it is a salutary reminder of the necessity of critical and reflexive thinking and an example of fruitful cooperation between social sciences and medicine. While the medicalization of prevention has emerged as the definitive answer to the AIDS pandemic, the text retains all its relevance today.